2011
DOI: 10.1097/icu.0b013e328341426f
|View full text |Cite
|
Sign up to set email alerts
|

Are ocular injection anesthetic blocks obsolete? Indications and guidelines

Abstract: Sub-Tenon's block should be performed in the operating theatre in preference to retrobulbar or peribulbar anesthesia except for limited indications. When injection ocular block is deemed necessary, we feel that retrobulbar anesthesia with the technique described may be safer than peribulbar anesthesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 49 publications
(34 reference statements)
0
13
0
Order By: Relevance
“…Nevertheless, Retrobulbar block is related to more frequent major complications [ 35 ]; an analysis of 26,045 Sub-Tenon’s and 11,134 Needle Blocks, showed only 4 cases of retrobulbar haemorrhage in the former vs. 8 cases in the latter [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, Retrobulbar block is related to more frequent major complications [ 35 ]; an analysis of 26,045 Sub-Tenon’s and 11,134 Needle Blocks, showed only 4 cases of retrobulbar haemorrhage in the former vs. 8 cases in the latter [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…A Cochrane systematic review of RBA versus PBA for cataract surgery also concluded that there is little to choose between the two in terms of anesthesia and akinesia during surgery, measuring acceptability to patients, need for additional injections and development of severe complications (25). Furthermore, since all the above dangers are inherent when using the right needle length and shape with the correct technique, there are advocates for STA over PBA and RBA (2627). …”
Section: Discussionmentioning
confidence: 99%
“…Sub-tenon's blocks have gained popularity due to the improved safety profile when compared to the 'blind stick' of a retrobulbar injection [15,[19][20][21][22][23]. The technique used today was first described by Stevens [24,25] in 1992.…”
Section: Regional Blocksmentioning
confidence: 99%